Waste glass as partial replacement for fine aggregate in mortar - Shu Yuen, Ngang (2013)
Glass was one of the oldest man-made materials. It was a common product that can be found in variety of form. In Malaysia, less than 30% of the glass was recycle and causing solid waste impact to the environment. Research on using waste glass as aggregate has been attempted decades ago and recent research shows that it can be used as aggregate under certain measures to avoid alkali silica reaction damaging effect. In this study, the effectiveness of waste glass used as fine aggregate in mortar was studied. Four mixes mortar was prepared accordance to the percentage of replacement of 0%, 10%, 20% and 30% of waste glass as fine aggregate. The specimens were tested for its compressive strength and percentage of permeability porosity under condition of 7, 28 and 90 days age of water curing. The specimens also tested for alkali silica gel expansion. It was found out that the compressive strength and the porosity of the mortar with waste glass as fine aggregate achieved optimum result at 10% of replacement. In the finding of alkali silica gel expansion, all the mix percentage does not exceed the 0.1% limit expansion. This shows that waste glass was suitable for partially replacing fine aggregate in mortar.